IMPROVING WRITING ABILITY USING STUDENT GUIDED STRATEGY AT CLASS IV SD NEGERI TIDUNG MAKASSAR - Salmiati Salmiati; Sundari Hamid; Asdar Asdar (Teaching English as a Foreign Language Overseas Journal, 2022)
This study examines the ability to write descriptive essays using the strategy of guided writing activity for fourth grade students of SD Negeri Tidung Makassar City. The main problem in this study is whether by using the strategy of guided writing activities students' ability to write descriptive essays can be increased. The purpose of this study was to improve the ability to write descriptive essays in Indonesian for class IV SD Negeri Tidung Makassar. This type of research is classroom action research that is recycled/cycle, which includes planning, implementation, observation and reflection. The focus of the research in this study was teachers and students. The research subjects were all fourth grade students of SD Negeri Tidung Makassar who were recorded in the even semester, totaling 34 students consisting of 18 male students and 16 female students. Data collection techniques through observation and tests. The data analysis technique used is a qualitative description analysis technique. The guided writing activity strategy learning model goes through 5 stages, namely: pre-writing, drafting, revision, editing and publication. In cycle I it is in the less category, cycle II is in the sufficient category. Thus it can be concluded that the results of the research show that guided writing activity strategies can improve the ability to write descriptive essays for fourth graders of SD Negeri Tidung Makassar as seen from the results of essay writing tests in each cycle.